1993
DOI: 10.1128/jvi.67.3.1175-1184.1993
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity in human T-cell leukemia/lymphoma virus type II

Abstract: DNA from the peripheral blood mononuclear cells of 17 different individuals infected with human T-cell lymphoma/leukemia virus type II (HTLV-II) was successfully amplified by the polymerase chain reaction (PCR) with the primer pair SK110/SK111. This primer pair is conserved among the pol genes of all primate T-cell lymphoma viruses (PTLV) and flanks a 140-bp fragment of DNA which, when used in comparative analyses, reflects the relative degree of diversity among PTLV genomes. Cloning, sequencing, and phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 51 publications
2
24
1
Order By: Relevance
“…The HTLV-IIa sequences were more similar to the sequence of the prototypic MoT isolate, whereas the HTLV-IIb sequences were closer to the sequence of the NRA isolate. This env-based clustering was further supported by Dube et al, who examined 140-bp pol fragments from 17 Amerindians and North Americans and demonstrated that the HTLV-II sequences of the Amerindian samples were similar to the subtype IIb sequence, while the HTLV-II sequences of the North American samples were a mixture of subtype IIa and IIb sequences (8).…”
mentioning
confidence: 58%
“…The HTLV-IIa sequences were more similar to the sequence of the prototypic MoT isolate, whereas the HTLV-IIb sequences were closer to the sequence of the NRA isolate. This env-based clustering was further supported by Dube et al, who examined 140-bp pol fragments from 17 Amerindians and North Americans and demonstrated that the HTLV-II sequences of the Amerindian samples were similar to the subtype IIb sequence, while the HTLV-II sequences of the North American samples were a mixture of subtype IIa and IIb sequences (8).…”
mentioning
confidence: 58%
“…We cannot explain this difference, although no significant sequence homologies exist between the CIEs of HTLV-1 and the whole sequence of HIV. There are significant sequence homologies among HTLV-1 and the related retroviruses simian T-cell leukemia virus type 1, HTLV-2, and bovine leukemia virus (12). Like HTLV-1, the HTLV-1-related retroviruses are not produced at detectable levels in PBMCs of the infected host but are often expressed when these cells are cultured in vitro (24,68,74).…”
Section: Discussionmentioning
confidence: 99%
“…HTLV-II is endemic in both native North and South Americans and Central African pygmies (with epidemic spread in IV drug users); subtype D, the most divergent, is found in Efe pygmies living not far from bonobos in the Congolese rain forest ( Vandamme et al, 2000). HTLV-II heterogeneity in the Americas is greater than in HTLV-I and comparable to HTLV-I/STLV-I in the Old World, suggesting that type II has been in the Western Hemisphere longer and was brought over by the original migrants, while HTLV-I was introduced more recently (Dube et al, 1993;Vandamme et al, 2000). Molecular clock estimates suggest that HTLV-II was carried out of Africa at least 58 kya and the American subtypes diverged between 12-38 kya, after the first human migrations to the New World.…”
Section: Viruses That Use Reverse Transcriptionmentioning
confidence: 99%